Maxillary premolar resorption by canines: three case reports - M. E. COOKE & S. J. NUTE (Paediatric Dentistry, 2005)
Palatal displacement of one or both maxillary canines is reported in 1% to 3% of North European [1] and North American [2] population samples. Eighty per cent of impacted canines are palatal, whereas the remaining 20% are buccal [3].